The Role of Digital Organizational Culture in Organizational Development In light of Digital Transformation adoption in Egypt - Salah El Din, Passant (The Arab Journal of Administration, 2025)
Purpose: The main purpose of this research is to examine the role of Digital Organizational Culture in Organizational Development, In light of Digital Transformation processes. An applied study to the Egyptian ministries that undergo the digital capacity building preparation program for the transfer to the new administrative capital city held by the Egyptian ministry for communication & Information Technology (MCIT) Design/ methodology/ approach: Discussion groups were held for experts in charge of training and qualifying governmental employees in light of the new digital environment in different Egyptian ministries. In addition, interviews for selected employees of different functional areas at different functional levels and an online research survey were conducted with various ministers’ employees. The research has used SPSS statistical tool to statistically analyze the collected data and test research hypotheses, Pearson correlation, and multiple regression analysis tests have been used. Findings: The findings of the research supported that Digital Organizational Culture has a significant impact on Organizational Development. Research limitations: The research is undertaken on governmental organizations and therefore is not necessarily represent other private or Non-governmental organizations. This research relied on self-reported data from participants in a cross-sectional sample. Empirical implications: In light of Digital Transformation and considering the unique characteristics of the new generation at work and the working environment in Egypt, the current research gives practical measurements and recommendations to the governmental sector in Egypt to support organizational development. Originality/Value: While Digital Organizational Culture in human resource practices has found its place in research interest, this paper fills the gap in the governmental sector particularly in the Egyptian governmental sector.